Apoprotein composition of very low density lipoproteins of human serum. - Kane, J P (1975)
Methods for quantitation of the major apoproteins of human serum very low density lipoprotein have been developed employing tetramethylurea, which delipidates the lipoprotein and selectively precipitates apolipoprotein B. Six soluble apoproteins are separated by electrophoresis in polyacrylamide gel. One of these is a previously unrecognized species of R-alanine (R4-alanine), more anionic than the R3-alanine polypeptide. Conditions of staining have been found which yield reproducibly linear chromogenic response with native lipoprotein and with each purified apoprotein. Recovery of protein in the seven species measured accounts for over 97% of the total in the very low density lipoprotein of normolipidemic individuals and in most samples from individuals with endogenous hyperlipemia. The mean content of apolipoprotein B in 43 samples from normolipidemic subjects was 36.9(+/-1.2 SEM)% of total protein, The distribution of the major soluble apoproteins as mean (+/-SEM) percentage of the soluble fraction was : R-serine, 5.3+/-o.5; arginine-rich, 20.6+/-1.0; R-glutamic, 10.6+/-0.4; R2-alanine, 28.3+/-0.7; R3-alanine, 26.9+/-0.5; and R4-alanine, 8.0+/-0.5. Distribution of the apoproteins was a function of particle diameter of very low density lipoprotein in fractions separated by gel permeation chromatography and by density gradient ultracentrifugation. In fractions below 700-800 A, apolipoprotein B comprised an increasing percentage of the total protein with decreasing particle diameter. Among the soluble proteins the percentage of the arginine-rich and R-serine polypeptides increased and that of the R-glutamic polypeptide declined progressively with decreasing particle size. Apoprotein distribution was similar in fractions of similar particle size from normolipidemic and hyperlipemic subjects with the exception that all fractions from the hyperlipemic subjects contained more R-serine and some, more arginine rich polypeptide. Even in the absence of chylomicrons, the distribution of soluble apoproteins in particles of diameters greater than 700-800 A was usually similar to that of the smallest particles. This suggests that the largest particles may include products of the partial catabolism of chylomicrons.